GENE-63. GENOMIC CHARACTERIZATION OF HUMAN BRAIN METASTASES IDENTIFIES NOVEL DRIVERS OF LUNG ADENOCARCINOMA PROGRESSION. (11th November 2019) - Nayyar, Naema; Shih, David; Bihun, Ivanna; Dagogo-Jack, Ibiayi; Gill, Corey; Aquilanti, Elisa; Bertalan, Mia; Kaplan, Alexander; D'Andrea, Megan; Chukwueke, Ugonma; Ippen, Franziska; Alvarez-Breckenridge, Christopher; et al.
Abstract: Although lung adenocarcinomas frequently metastasize to the brain, treatment options for lung adenocarcinoma brain metastases are limited. We discovered novel candidate drivers of progression by using case-control analyses to compare whole-exome sequencing data from a cohort of 73 lung adenocarcinoma brain metastases to a control cohort of 503 primary lung adenocarcinomas. We identified 3 genomic regions with significantly more frequent amplifications in brain metastases compared to the control cohort: MYC (12% vs 6%), YAP1 (7% vs 0.8%) and MMP13 (10% vs 0.6%). We also identified CDKN2A/B as a region deleted at a significantly greater frequency in brain metastases compared to primary lung adenocarcinomas (27% vs 13%, respectively). We confirmed frequent amplifications of MYC and YAP1/MMP13 in an independent validation cohort of 105 lung adenocarcinoma brain metastasis samples using fluorescence in situ hybridization. We further validated that MYC, YAP1 and MMP13 can drive brain metastases in a patient-derived xenograft mouse model. We found a higher incidence of metastases to the brain in mice receiving intracardiac injections of tumor cells expressing the candidate drivers compared to tumor cells expressing LacZ as a control. These results indicate that somatic alterations can drive lung adenocarcinomas to metastasize to the brain. The candidate brain metastasis drivers that we identified may serve as therapeutic targets in patients with lung adenocarcinomas who develop this devastating complication.